A novel isocyanide/Ag2CO3-promoted addition of heteroatoms to alkynes under mild conditions. Issue 3 (5th January 2023) - Lei, Jie; Xu, Jia; Luo, Ya-Fei; Li, Jie; Wang, Jing-Ya; Li, Hong-yu; Xu, Zhi-Gang; Chen, Zhong-Zhu
Abstract : A silver(i ) isocyanide complex was used as a catalyst to activate alkynes rapidly and carry out intramolecular electrophilic addition of alkynes to synthesize various different-sized rings in excellent yields under mild conditions. Abstract : A facile and practical isocyanide/Ag2 CO3 -promoted atom-economic addition of heteroatoms to alkynes has been developed for the construction of high-value scaffolds. In contrast to the reported methods, this strategy featured efficient and green characteristics, e.g., broad functional group compatibility, rapid and quantitative conversion, use of an eco-friendly solvent (EtOH), and an isocyanide/Ag2 CO3 catalytic transformation. Moreover, the catalyst loading of Ag2 CO3 could be decreased to 1 mol% with the aid of isocyanide. Therefore, in principle, numerous common classes of additions of a nucleophilic element-hydrogen to alkynes could likewise be amenable to this catalyst system.